Protection measures at archaeological sites considered within the preventive actions against the 2015 El Niño phenomenon in the Lambayeque Region - Coahila Osorio, Alberto (2018)
The Lambayeque region, which possesses a rich cultural heritage, contains archaeological evidence that helps build our identity; this can occur thanks to the presence of societies that evolved and put forth the knowledge they obtained through research. Therefore, it is important to protect such archeological evidence and ensure its durability for the take profit of future generations. The national government, through the Ministry of Culture, launched a program for the protection of archaeological heritage in the northern coast of the country in order to mitigate the impact of rains of El Niño (ENSO –El Niño Southern Oscillation). Activities in the Lambayeque region were channeled through the Executive Unit 005 Naylamp from late 2014 until early 2016, and covered a total of 28 of the most vulnerable archaeological sites. The preservation procedures carried out allowed the selected areas to prepared in the best conditions and with better results against ravages of nature. Finally, we reflect about the territoriality of archaeological heritage in the Lambayeque region, according to the spatial-physical diagnosis developed in 2015 as part of the Master Plan for a Better Management of Archaeological Heritage of the Region Lambayeque.